DEVELOPMENT OF A MIXTURE OF PLASTER AND HUSK ASH FOR USE LOW COSTS PLASTER MOULD IN THE LOCAL CERAMIC INDUSTRY - Phinsakul, Sanit (Life Sciences and Environment Journal, 2017)
The objectives of this research were to: 1) test a formula of plaster mixed with husk ash in different ratios; 2) test the physical property of the plaster mixed with husk ash;3) create a mold from plaster mixed with husk ash; and 4) to compare the efficiency of molds using the plaster mixed with husk ash and that of general plaster. The samples in this study were 25 of both types. Physical properties included formability of mold, setting time, strength, postdrying weight, casting rate, and formability of ceramics. The results showed that the proper formula consisted of 90% of plaster and 10% of husk ash. The setting time of the mold was 23 minutes at an average strength of 39.30±5.37 kg/cm², an average density of 1.13±0.04 g/cm³, and 10-minute molding time. The comparison of formability of ceramics revealed that there were no significant differences between the two types of molds.